Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702337
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Materials Experience

Abstract: A growing number of HCI scholars have started to take materiality as an entry point for acquiring a deeper understanding of the possibilities and constraints of design. Steadily moving beyond a distinction between the physical and the digital, a few have also started to look at materials as part of the unfolding of social and cultural practices. Yet, to date, relatively little is known about how these practices develop within the situated experience of materials, and how this situational whole can be supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 55 publications
0
111
0
8
Order By: Relevance
“…Finally, this research focussed on materials, presented to the participants in isolated settings. However, in real life, we experience materials embodied in products, within a specific situational whole [34,37]. In other words, the study results would be different when a material is situated within a context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this research focussed on materials, presented to the participants in isolated settings. However, in real life, we experience materials embodied in products, within a specific situational whole [34,37]. In other words, the study results would be different when a material is situated within a context.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the aesthetic universals in the materials domain may refer to the relationships between visual and tactile qualities in material appraisals. Subject to our experiences with and through materials [37,38] some assumptions are developed on how a particular material would feel when it is touched based on its visual qualities. In product design, the visual-tactile (in)congruity between visual and tactile sensations is known to elicit certain emotions such as surprise.…”
Section: Symmetry Originalitymentioning
confidence: 99%
“…In her research Karana found that when users appraise a material, typically there is a link between use and associative descriptions, and manufacturing process descriptions and sensorial descriptions. Further, four experiential levels of material experience were identified, namely sensorial, affective, interpretive and performative (Giaccardi & Karana, 2015). The sensorial level refers to the phases in which users' sensorial modalities, i.e.…”
Section: Materials Experiencementioning
confidence: 99%
“…The MDD method is a new methodology for materials exploration and design focusing on the notion of Materials Experience and combining practical experimentation, user studies and envisioning. Since materiality highly contributes to the definition of Product Experience (Desmet and Hekkert, 2007) the concept of Materials Experience arises as "the experience that people have through and with materials" (Karana, 2009;Karana, Pedgley, and Rognoli 2015), considering senses, meanings, emotions, and ways of doing (Giaccardi and Karana, 2015). A hands-on approach appears to be crucial in the MDD method to understand materials and develop them further.…”
Section: Materials Tinkering As Educational Practicementioning
confidence: 99%